SALAM DAN UNGKAPAN PERPISAHAN DALAM BAHASA INGGRIS DAN BAHASA JEPANG (SUATU ANALISIS KONTRASTIF) - Sumilat, Aprilia Olijane; Pelealu, Hetty; Lasut, Theresia M.C (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â ABSTRACTÂ Â Â Â This title of this research is â€œSalam dan Ungkapan Perpisahan dalam Bahasa Inggris dan Bahasa Jepang: â€œContrastive Analysisâ€. The aims of this study are to identify, describe and contrast the forms and pattern of greetings and leave-takings in English and Japanese Language. This research uses descriptive method and contrastive analysis. The data in English were collected from books related to sociolinguistics, book of speaking, and source from internet. The data in Japanese Language were collected by doing direct and indirect interview, and source from internet. The data were analyzed by using the conseptsof Fishman, and Wardhaugh. The result of this research shows that greetings and leave-takings in English and Japanese Language have two forms which are formal and informal. In addition, the writer finds that there are three patterns in English and Japanese Language on greetings. Those patterns are mutual formal greetings, mutual informal greetings and the non mutual greetings. The patterns of English leave-taking are the same as their greetings. On the other hand, Japanese Language has only two patterns of non mutual leave-takings, formal and informal. Greetings and leave-takings in English and Japanese Language have differences. For instance, greetings and leave-takings in English are various. Meanwhile in Japanese language are limited.Keywords : Greetings and leave-takings English, Japanese Language, Contrastive Analysis